2019
DOI: 10.3855/jidc.9810
|View full text |Cite
|
Sign up to set email alerts
|

Levels of different cytokines in women and men with asymptomatic genital infection caused by Chlamydia

Abstract: Introduction: Immune response to genital Chlamydia trachomatis infection is involved in both immunity and pathology. The cytokine profile during infection has been implicated in the disease outcome, either resolution or severe sequelae. Methodology: In total, 3900 patients were analyzed for presence of genital infections caused by Chlamydia using molecular assays. Interleukins (IL) IL-10, IL-17, IL-6, IL-2 and chemokine IP-10 were estimated by ELISA in urine, cervical swabs and semen samples. Statistical analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…These results are similar to those observed by Buckner et al ( 2011 ), where perceptible levels of IL-6, IL-8, IP10, and RANTES were detected. In addition, we observed that the cytokine response of the model in the presence or absence of a chlamydial infection was comparable to that previously observed in this and other human and mouse cell lines (Buckner et al 2013 , Hwang et al 2015 , Bua et al 2019 , Yang et al 2019 ). These results indicate that the A2EN cervical epithelium 3D model could serve as a suitable platform for studies of chlamydial infection.…”
Section: Resultssupporting
confidence: 88%
“…These results are similar to those observed by Buckner et al ( 2011 ), where perceptible levels of IL-6, IL-8, IP10, and RANTES were detected. In addition, we observed that the cytokine response of the model in the presence or absence of a chlamydial infection was comparable to that previously observed in this and other human and mouse cell lines (Buckner et al 2013 , Hwang et al 2015 , Bua et al 2019 , Yang et al 2019 ). These results indicate that the A2EN cervical epithelium 3D model could serve as a suitable platform for studies of chlamydial infection.…”
Section: Resultssupporting
confidence: 88%
“…These results are similar to those observed in Buckner et al [46], where perceptible levels of IL-6, IL-8, IP10 and RANTES were detected. We observed that the cytokine response of the model in the presence or absence of a chlamydial infection was similar to that previously observed in this and other human and mouse cell lines [53][54][55][56]. These results indicate that the A2EN cervical epithelium 3D model could serve as a suitable platform for studies of chlamydial infection.…”
Section: D Cervical A2en Cells Are Infected By Chlamydia Trachomatis and Neisseria Gonorrhoeaesupporting
confidence: 87%
“…IL-6 is overexpressed in mice with Chlamydia-related tubal factor infertility or humans who suffered from Chlamydia-related disease (94,95). IL-6 can also be detected in the semen and serum of asymptomatic patients with Chlamydia infection (96,97). Elevated IL-6 levels were found to play a protective role in controlling Chlamydia infection, given that IL-6 deficient mice were significantly more susceptible to Chlamydia infection through the airway than wildtype mice (98,99).…”
Section: Il-6mentioning
confidence: 99%